Augmented reality for everyone: creating geolocated data layers - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2011)
Smartphones have implemented augmented reality applications, with virtual layers overlapping real images. One of the uses of augmented reality is to display information related to the place where we are, superimposed on an image of reality (captured from the camera of the device). Although it may seem complex, it is easy for any internet user to publish location-based content through augmented reality browsers like Layar or Wikitude. This text sets out some ways to do it.